2015
DOI: 10.1210/en.2015-1213
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Regulation of Marrow Fat in the Setting of PPARγ Agonist Treatment in Female C57BL/6 Mice

Abstract: The contribution of marrow adipose tissue (MAT) to skeletal fragility is poorly understood. Peroxisome proliferator-activated receptor (PPAR)γ agonists, associated with increased fractures in diabetic patients, increase MAT. Here, we asked whether exercise could limit the MAT accrual and increase bone formation in the setting of PPARγ agonist treatment. Eight-week-old female C57BL/6 mice were treated with 20-mg/kg · d rosiglitazone (Rosi) and compared with control (CTL) animals. Exercise groups ran 12 km/d whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 65 publications
3
80
0
Order By: Relevance
“…That said, it is interesting that the level of actual necrosis in the tibia of myeloma mice that served as sham control was higher than that measured in LIV, suggesting at least some capacity to deter the late stages of the pathology was evident. Alternatively, or in conjunction, there is evidence of spatial differences of marrow, not only within a given bone (62), but between bones (60), as well as the capacity of mechanical signals to influence bone morphology at these different sites. With evidence of the consequences of the disease evident in the axial skeleton, with some salutary benefit of LIV to protect skeletal components remote from the site of vibration, suggests circulatory factors may also be at play.…”
Section: Discussionmentioning
confidence: 99%
“…That said, it is interesting that the level of actual necrosis in the tibia of myeloma mice that served as sham control was higher than that measured in LIV, suggesting at least some capacity to deter the late stages of the pathology was evident. Alternatively, or in conjunction, there is evidence of spatial differences of marrow, not only within a given bone (62), but between bones (60), as well as the capacity of mechanical signals to influence bone morphology at these different sites. With evidence of the consequences of the disease evident in the axial skeleton, with some salutary benefit of LIV to protect skeletal components remote from the site of vibration, suggests circulatory factors may also be at play.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with access to a wheel will voluntarily run ~10 km per day 35, 48 . This level of exercise reduces rBMA number and size in both lean and diet-induced obese mice 35 , suggesting that energy stored within marrow adipocytes is readily mobilized under these conditions.…”
Section: Development and Regulation Of Bmat In Humans And Rodentsmentioning
confidence: 99%
“…OVX-induced osteoporosis studies have demonstrated that bone loss can occur prior to increases in MAT [24]. Exercise has been shown to significantly suppress MAT volume and induce bone formation in certain mouse models, suggesting that a double-edged sword may be strengthening bones and decreasing MAT in MGUS or MM patients via diet and exercise to improve bone outcomes [25]. …”
Section: Understanding the Bone Marrow Niche Cellular Componentsmentioning
confidence: 99%
“…In order to combat the potential that elevated MAT impacts tumor growth in MM, a number of approaches currently exist in the clinic. Weight loss via diet and exercise has been shown to decrease elevated MAT resulting from high fat diet or PPARγ agonists [25, 118]. Elevated MAT can also be treated with the anti-diabetic drug metformin, which is able to significantly decrease MAT in a diet-induced obesity mouse model (unpublished data).…”
Section: Targeting Bm Elements To Control Disease (Bone/niches/adimentioning
confidence: 99%